2023
DOI: 10.3390/nu15143148
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dietary Inflammatory Index and Dietary Oxidative Balance Score with All-Cause and Disease-Specific Mortality: Findings of 2003–2014 National Health and Nutrition Examination Survey

Abstract: To clarify the effects of dietary inflammatory and pro-oxidative potential, we investigated the impact of the Dietary Inflammation Index (DII) and the Dietary Oxidative Balance Score (DOBS) on all-cause and disease-specific mortality. For DII and DOBS, 17,550 and 24,527 participants were included. Twenty-six and seventeen dietary factors were selected for scoring. Cox proportional hazards regression models were used. DII and DOBS were significantly associated with all-cause, CVD, and cancer mortality in this n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 69 publications
(78 reference statements)
2
2
0
Order By: Relevance
“…In addition, we further validated that individuals who are exposed to higher levels of dietary or lifestyle OBS may potentially exhibit a reduced risk of mortality. Consistent with our study results, Wang et al demonstrated that dietary OBS was negatively linked to deaths from all causes and CVD [29]. According to a meta-analysis, adhering to a healthy lifestyle has been found to significantly decrease the mortality rate among middle-aged women [44].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, we further validated that individuals who are exposed to higher levels of dietary or lifestyle OBS may potentially exhibit a reduced risk of mortality. Consistent with our study results, Wang et al demonstrated that dietary OBS was negatively linked to deaths from all causes and CVD [29]. According to a meta-analysis, adhering to a healthy lifestyle has been found to significantly decrease the mortality rate among middle-aged women [44].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our results, a cohort study reported a significant inverse dose-response correlation between elevated OBS and the occurrence of new-onset hypertension [13]. Similarly, another study reported a progressive decline in the risk of all-cause mortality as the intake of dietary OBS increased [29]. In summary, our findings provide compelling evidence to endorse a public health recommendation that dietary and lifestyle antioxidants can effectively mitigate the risk of CMRFs and enhance the prognosis of patients.…”
Section: Discussionsupporting
confidence: 90%
“…However, there were no notable links found between DOBS and CVD (HR 0.71, 95% CI 0.49–1.04) or cancer mortality (HR 0.69, 95% CI 0.47–1.01). 15 The cross-sectional analysis conducted by X. Wang has revealed the significant and accelerated impact of a pro-oxidative dietary (lower DOBS) on the aging process. 11 These studies provide empirical evidence supporting the beneficial impact of DOBS on outcomes in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…10 The DOBS scoring system is a dependable method for quantifying the potential antioxidant capacity of daily dietary intake, and has recently been utilized to evaluate its impact on health conditions including biological aging, 11 CVD, 12 cancer 13 and mortality. 14,15 There also exists a co-dependency between oxidative stress and CVD. Prior researches have provided evidence that the pathogenesis of CVD is facilitated by oxidative stress-induced damage to endothelial and smooth muscle cells, 16,17 and a higher intake of dietary antioxidants has been linked to a decreased risk of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed information and method of application can be obtained from the website: https://www.cdc.gov/nchs/nhanes/index.htm . The survival status and cause of death in NHANES can be determined by matching National Death Index (NDI) records ( 27 ).…”
Section: Methodsmentioning
confidence: 99%